1990
DOI: 10.1042/bj2690393
|View full text |Cite
|
Sign up to set email alerts
|

Cell-wall polysaccharides and glycoproteins of parenchymatous tissues of runner bean (Phaseolus coccineus)

Abstract: 1. Polymers were solubilized from the cell walls of parenchyma from mature runner-bean pods with minimum degradation by successive extractions with cyclohexane-trans-1,2-diamine-NNN'N'-tetra-acetate (CDTA), Na2CO0 and KOH to leave the a-cellulose residue, which contained cross-linked pectic polysaccharides and Hyp-rich glycoproteins. These were solubilized with chlorite/acetic acid and cellulase. The polymers were fractionated by anion-exchange chromatography, and fractions were subjected to methylation analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0
3

Year Published

1993
1993
2013
2013

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(21 citation statements)
references
References 40 publications
1
17
0
3
Order By: Relevance
“…These results are very coherent with the legume seed sugar compositions reported in the literature [11,15,19,20,25,27,33,37]. BHATTY [4] inferred that the lentil cell wall was probably composed of arabinan and arabinogalactan polysaccharides, because such polysaccharides are commonly distributed in the primary cell wall of cotyledonous plants.…”
Section: -Results and Discussionsupporting
confidence: 79%
“…These results are very coherent with the legume seed sugar compositions reported in the literature [11,15,19,20,25,27,33,37]. BHATTY [4] inferred that the lentil cell wall was probably composed of arabinan and arabinogalactan polysaccharides, because such polysaccharides are commonly distributed in the primary cell wall of cotyledonous plants.…”
Section: -Results and Discussionsupporting
confidence: 79%
“…colleagues (Stevens and Selvendran, 1984;Ryden and Selvendran, 1990) systematically studied wall polysaccharides extracted from diverse tissues of different plants, including runner bean (Phaseolus coccineus), mung bean (Vigna radiata), cabbage (Brassica oleracea), and tomato (Solanum lycopersicum). Based on these studies, the authors suggested the presence of wall polysaccharide-protein and wall polysaccharide-polyphenol-Hyprich glycoprotein complexes in those plant tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Quantidades pequenas de xiloglicano foram encontradas em feijões, verificando-se, também, a presença de xilogalacturonanos e xilanos (RYDEN & SELVENDRAN, 1990;GOONERATNE et al, 1994 b ; MCDOUGALL & SELVENDRAN, 2001). …”
Section: Ligações Cruzadasunclassified
“…A literatura descreve a estrutura de parede celular de Phaseolus coccineus e Vigna radiata como sendo formada por pequenas quantidades de xiloglicanos e xilanos (RYDEN & SELVENDRAN, 1990;GOONERATNE et al, 1994 b ). É provável que este padrão também se repita em…”
Section: Composição Dos Polímeros Do Cotilédoneunclassified
See 1 more Smart Citation